Spiritual Tourism: Exploring Sacred Sites Worldwide - Jihana, Tsamira (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2025)
Spiritual tourism has emerged as a significant sector within the global travel industry, driven by an increasing interest in spiritual experiences and cultural immersion. This paper explores various sacred sites around the world, examining their historical, cultural, and spiritual significance. By analyzing different pilgrimage routes and destinations, the paper highlights how these sites contribute to personal transformation and community cohesion. In addition, the study considers the impact of commercialization on spiritual tourism and the potential for sustainable practices. Through a comprehensive review of existing literature and qualitative methodologies, this study aims to shed light on the motivations behind spiritual travel and its implications for local communities. Ultimately, the findings underscore the importance of preserving the integrity of sacred sites while accommodating the growing demand for spiritual tourism.